Disposal of layer droppings reared in case and impact on environmental pollution (Journal of the Bangladesh Agricultural University, 2010)
A study evaluated the droppings disposal in layer farm and measures adapted to protect environmental pollution. Data were collected from 20 randomly selected layer farmers by a semi structured personal interview schedule from Sadar upazilla of Mymensingh. The independent variables such as age and gender of farmers, family size educational qualification occupation etc. and the dependent variables such as flock size, age of birds, feed consumption, egg and dropping production, cleaning of dropping etc. were studied. The feed consumption and droppings production/layer/day were 116.54 and 151.65g, respectively. Hen housed egg production was 80.55%. The cost for cleaning, price of droppings and profit on droppings sale/layer/day were Tk 0.01, 0.07 and 0.07 respectively. Half of farmer received maximum earning from droppings in winter. Most of the farmers had single storied house and used ceiling fan. Most of the farmers clean droppings in alternate day in the morning by the male worker using belcha to minimize environmental pollution and half of them used disinfectants. Average time required/day to clean droppings was 83.00 minute. Majority of the farmer consider cleaning of droppings to be a real problem for odour and gas (NH3) emission. Majority farmers stored droppings at high land as an open pit. Average distance between pit and shed was 58.33m. The highest proportion of the farmers used droppings in the crop field by composting while others sold to fisheries. Majority of the respondents opined that feed, droppings, dead birds, medicinal wastes and odour do not cause environmental pollution. Droppings disposal is a real problem for aesthetic, public safety and environmental point of view. Cleaning technique and tools needed to be modernized for efficient and cost effective cleaning. Standard method needed to be introduced for proper treatment and use of droppings to maximize its use and benefit. Keywords: Droppings disposal; Environmental pollution; Caged rearing DOI: 10.3329/jbau.v7i2.4735 J. Bangladesh Agril. Univ. 7(2): 281-290, 2009